2022
DOI: 10.1111/bjet.13277
|View full text |Cite
|
Sign up to set email alerts
|

Infusing educational technologies in the heart of the university—A systematic literature review from an organisational perspective

Abstract: Educational technologies have experienced unprecedented prominence on university agendas with many institutions motivated to keep the lessons learned from the COVID-19 sparked transition with regard to online teaching. In response to this renewed interest in ensuring the longevity of educational technologies in higher education, this systematic review analysed the various organisational factors-for example, leadership, infrastructure, strategy-considered essential in the literature for the successful implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…This was supported in thematic narrative findings centered on, “a question of professional (dis)regard” where WB responds to an interview question with, “I know, what I know….” The results additionally suggest, specifically, a discussion regarding representation in governance and an expression of unspoken, external factors. This indicated that IDs could enhance their professional outcomes by consistently, cohesively, and cooperatively engaging in critical inquiry into the institutional norms they view as obstructing their professional work and sense of self (Deacon et al, 2023; Intentional Futures, 2016). This shift is necessary to distance themselves from the perception that they are merely “glorified IT personnel” (Intentional Futures, 2016, p. 3) and instead develop institutional literacy to actively participate in institutional governance.…”
Section: Discussion and Hrd Implicationsmentioning
confidence: 99%
“…This was supported in thematic narrative findings centered on, “a question of professional (dis)regard” where WB responds to an interview question with, “I know, what I know….” The results additionally suggest, specifically, a discussion regarding representation in governance and an expression of unspoken, external factors. This indicated that IDs could enhance their professional outcomes by consistently, cohesively, and cooperatively engaging in critical inquiry into the institutional norms they view as obstructing their professional work and sense of self (Deacon et al, 2023; Intentional Futures, 2016). This shift is necessary to distance themselves from the perception that they are merely “glorified IT personnel” (Intentional Futures, 2016, p. 3) and instead develop institutional literacy to actively participate in institutional governance.…”
Section: Discussion and Hrd Implicationsmentioning
confidence: 99%
“…Digital technology has become a large part of conventional learning ecosystems due to COVID‐19's impact (Deacon et al, 2022). With this transformation have come concerns about the collection and uses of student data (Jones et al, 2019; Lupton, 2021; Trainor, 2015).…”
Section: Wearable Technology In Higher Educationmentioning
confidence: 99%
“…Each of these syntheses addressed some aspect of technology integration in higher education, but several of them advocated for greater research on specific topics, organizational and otherwise, for more specific data on learners in online and technology‐enhanced spaces (Deacon et al, 2022; Martin et al, 2020). Our synthesis helps fill a gap by exploring students' perspectives on student privacy in online, hybrid and technology‐enhanced courses.…”
Section: Introductionmentioning
confidence: 99%
“…Their review of over 500 articles resulted in 51 articles, and they found that there were three themes across the MOOC learner literature: course engagement, satisfaction and achievement, and motivation. Deacon et al (2022) also employed a systematic literature review to explore the organizational mechanisms that made it possible to integrate educational technology. Their study included a review of 1614 papers published in ‘five prominent educational technology journals in the last decade’ (Deacon et al, 2022, p. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation